Pengaruh Social Media (Instagram), Celebrity Endorse, Dan Harga Terhadap Keputusan Pembelian Lozy Hijab (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang Angkatan 2019) - Alviona Alviona; Muhammad Agus Salim; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted to determine the effect of social media (instagram), celebrity endorsements, and prices on purchasing decisions for Lozy Hijab. The number of samples was determined using the Maholtra formula with a purposive sampling method and the results obtained were 95 respondents. Data was obtained by distributing questionnaires to Students of the Faculty of Economics and Business Class of 2019 at the Islamic University of Malang. The type of research used in this research is quantitative. Data analysis in this study used SPSS IBM V.26 for windows. The data testing technique used is validity test, reliability test, multiple linear regression analysis, normality test, classical assumption test, hypothesis test, and the coefficient of determination (R2). In this study, the results showed that social media (instagram), celebrity endorsements, and prices simultaneously influence the purchasing decision of Lozy Hijab. Social media (Instagram) has a partial effect on purchasing decisions, celebrity endorses have no partial effect on purchasing decisions, and prices have a partial effect on purchasing decisions.  Keywords: Social Media (Instagram). Celebrity Endorsements, Pricing, and Purchase Decisions.